The Lungs: Anatomy, Function, Disorders, and Care - Akram, Muhammad; Ahmed, Misbah; Umaru, Isaac John (African Journal of Medicine, Surgery and Public Health Research, 2025)
The lungs play a crucial role in the respiratory system, facilitating oxygen intake and carbon dioxide removal. This article explores lung anatomy, including the differences between the right and left lungs, and details their function in gas exchange. It also highlights common lung disorders such as asthma, COPD, and lung cancer, along with their symptoms, diagnostic tests, and treatments. Additionally, it provides essential tips for maintaining lung health, such as quitting smoking, exercising, and staying hydrated. Understanding lung function and care is vital for overall well-being and disease prevention.